1989
DOI: 10.1111/j.1365-2338.1989.tb00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations concerning soil‐borne viruses in sugarbeet in Sweden1

Abstract: Some experiments with soil‐borne beet viruses in cement tubes in a wire netting enclosure are described. It is confirmed that rhizomania (virus + vector) originating from German soil can survive and cause rhizomania in Sweden. Antisera produced in 1987 to one German BNYVV isolate and to one Swedish soil‐borne beet virus isolate, 86‐109, which is distinct from BNYVV, were used to check ELISA reactions in the tube beets. Positive ELISA was obtained not only for BNYVV but also for the 86‐109 virus from tubes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…One serotype contains the German isolates Wierthe and Dornheim, and the second group comprises the German isolate Ahlum, BSBV-N, the Swedish isolate 86-109 (Lesemann et al, 1989) and the Belgian isolate 1530 (Hutchinson et al, 1990). These serotypes are distinct from BNYVV and from the soil-borne sugar beet viruses isolated in California (Lesemann et al, 1989;Lindsten, 1989). However, in the absence of reciprocal serological tests (owing to the lack of availability of antisera to all of the isolates examined), such a subdivision is tentative.…”
mentioning
confidence: 94%
“…One serotype contains the German isolates Wierthe and Dornheim, and the second group comprises the German isolate Ahlum, BSBV-N, the Swedish isolate 86-109 (Lesemann et al, 1989) and the Belgian isolate 1530 (Hutchinson et al, 1990). These serotypes are distinct from BNYVV and from the soil-borne sugar beet viruses isolated in California (Lesemann et al, 1989;Lindsten, 1989). However, in the absence of reciprocal serological tests (owing to the lack of availability of antisera to all of the isolates examined), such a subdivision is tentative.…”
mentioning
confidence: 94%
“…Beet soil-borne virus (BSBV) which was first described in England (Ivanovic & Macfarlane, 1982) is apparently widely spread in Europe (Henry, Jones & Coutts, 1986;Verhoyen, van den Bossche & van Steyvoort, 1987;Lindsten, 1989;Lesemann, Koenig, Lindsten & Henry, 1989). The virus resembles beet necrotic yellow vein virus (BNYVV), the causal agcnt of sugarbeet rhizomania, morphologically and in its transmissibility by Polymyxa beta (Ivanovic & Macfarlane, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…However, no relationships have been found between the two viruses in serological or nucleic acid hybridisation tests and the ss and dsRNAs associated with the two viruses yield different electrophoretic patterns (Henry & Hutchinson, 1989; Lesemann et a f . , 1989;Li et al, 1990;Kaufmann et al, 1992h). Also, the RNAs of BNYVV are polyadenylated (Putz, Pinck, Fritsch & Pinck, 1983) whereas those of BSBV are apparently not (Kaufmann et al, 19926).…”
Section: Introductionmentioning
confidence: 99%
“…The Ahlum isolate proved to be serologically closely related to beet soil-borne virus (BSBV), which was first described in England (Ivanovic et al, 1983 ;Henry et al, 1986) and has since been found in all sugarbeet growing areas worldwide (e.g. Verhoyen et al, 1987 ;Lindsten, 1989 ; present authors' unpublished observations). The second virus (Wierthe isolate) was originally thought to be a serologically distantly RNA-dependent RNA polymerase region.…”
Section: Introductionmentioning
confidence: 99%